2015
DOI: 10.4162/nrp.2015.9.3.304
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and changes in dietary behavior and anthropometric measures among Chinese international students in South Korea

Abstract: BACKGROUND/OBJECTIVESInternational students face dissimilar food environments, which could lead to changes in dietary behaviors and anthropometric characteristics between before and after migration. We sought to examine the risk factors, including dietary behaviors, acculturation, and demographic characteristics, related to overweight subjects residing in South Korea.SUBJECTS/METHODSWe conducted a cross-sectional study, collecting data from 142 Chinese international students (63 males, 79 females) in 2013.RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
3
11
0
6
Order By: Relevance
“…A mobile population, consisting of international students, moves from their origin countries to carry on their higher studies in host countries [ 9 ]. Earlier, a study stated that migration may have negative impact on health status because of dissimilar environment [ 10 ]. One study reported that a majority of students who migrate to the United States (US) gain weight and also there is a gradual shift in the dietary patterns of international students to an American diet [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A mobile population, consisting of international students, moves from their origin countries to carry on their higher studies in host countries [ 9 ]. Earlier, a study stated that migration may have negative impact on health status because of dissimilar environment [ 10 ]. One study reported that a majority of students who migrate to the United States (US) gain weight and also there is a gradual shift in the dietary patterns of international students to an American diet [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of post-graduate scholarships awarded at King Saud University has dramatically increased for international students, resulting in an increased number of international students attending the university. A study has been conducted on the dietary behaviours and cultures of immigrants and international students and concluded that the adjustment of foreign students to new cultures and the effect of nutrition risk factors on their dietary behaviour cannot be underestimated (1) . Adverse changes in dietary patterns have been reported, including reduced intake of fruits and vegetables, increased intake of sweets and fats and increased energy level.…”
mentioning
confidence: 99%
“…In the study comparing Korean and Chinese female high school students, the score for dietary habits was higher in Chinese students (3.74 points) compared to Korean students (3.12 points) [25]. In the study on Korean and Chinese students, the most important meal of the day was lunch in Korean students while breakfast in Chinese students, and the combination of food groups at each meal was considered more importantly in Chinese students compared to Korean students [2627]. This was similar to the results of the study in which CPW showed higher scores for questions such as ‘Do you eat breakfast every day?’ and ‘Do you consider combination of food groups at each meal?’ compared to KPW.…”
Section: Discussionmentioning
confidence: 99%